PENGARUH INVESTASI ASING, JUMLAH PENDUDUK, INFLASI, DAN ANGKATAN KERJA TERHADAP PENGANGGURAN DI SWEDIA - Octaviana, Farida Nur; Hasmarini, Maulidyah Indira (ITB AAS Indonesia Surakarta, 2024)
This research aims to analyze how much foreign investment, population, inflation, and labor force influence unemployment in Sweden for the period 1991-2022. The data set used comes from the World Bank, the method used in this study is a quantitative approach with time series data analysis using EViews 12, which is analyzed using Error Correction Model (ECM) regression analysis method to investigate the short term and long term impacts of independent variables, including foreign investment, population, inflation, and labor force, on unemployment. The findings show indicate that there is no evidence to conclude that the labor force affects unemployment in either the short or long term. In the short term, foreign investment and population influence unemployment. In the long term, foreign investment and inflation influence unemployment.